Pernikahan Anak dalam Perspektif Hukum Islam dan Perlindungan Perempuan Indonesia Era Kontemporer - Nurhalim (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2025)
This study examines the practice of child marriage in Indonesia from the perspective of Islamic law and women’s protection in the contemporary era. The research departs from the ongoing tension between classical Islamic legal interpretations, state regulations, patriarchal cultural traditions, and the increasing global concern for gender justice and child protection. The study aims to analyze how child marriage is understood within contemporary Islamic legal discourse and to explore the relevance of maqāṣid al-sharī‘ah in reconstructing Islamic family law oriented toward women’s protection. This research employs a qualitative method using normative-juridical and socio-legal approaches. Primary data were obtained from Islamic legal sources, Indonesian marriage regulations, and religious court decisions concerning marriage dispensation, while secondary data were collected from international journal articles, academic books, and contemporary scholarly studies related to Islamic law, gender, and child marriage. Data were analyzed through content analysis and descriptive-interpretative methods. The findings reveal that child marriage practices in Indonesia are still strongly influenced by textual and conservative interpretations of Islamic law that prioritize biological maturity over psychological, educational, economic, and social readiness. The study further demonstrates that child marriage generates greater social harm than benefit, particularly for women, including educational deprivation, reproductive health risks, domestic violence, economic dependency, and psychological vulnerability. This research argues that the reconstruction of Islamic family law through maqāṣid al-sharī‘ah and gender justice approaches is necessary to ensure the protection of women’s rights and to maintain the substantive objectives of Islamic law within contemporary Muslim society